Assignment 3 Solutions 2009

2 1 2 2 2

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = ¶F s s V1 ¶T ss V1 ¶Q ss r pV1 c 1 b = 1 ¶f 2 (T - T ) ¶f F ¶f - Fs = 1s 2 s ; b = 2 = s ; b = 2 = 2 3 ¶F ss V ¶T ss V ¶T ss V 2 1 2 2 2 By subtracting the steady­state equation and defining deviat ion variables (like F = F - F ), we obtain the fo llowing equat ions: s dT 1 = a F + a 2 T + a 3Q 1 1 dt d 2 T = b F + b T + b T 1 21 32 dt Taking the Laplace transformat ion, sT ( s ) = a F ( s + a 2 T ( s ) + a 3Q ( s ) ) 1 1 1 s 2 ( s ) = b1 F ( s + b2 T ( s + b3T ( s ) T ) 1 ) 2 and rearranging, a 3 a 1 F ( ) + s Q ( ) s s - a 2 s - a 2 b b T ( s = 1 F ( s + 2 T ( s ) 2) 1) s - b s - b 3 3 T1 ( s = ) Replacing the first equation into the second equation and rearranging again, T2 ( s = ) ù b b é a a 3 1 F ( s + 2 ê 1 F ( s + ) ) Q ( s )ú s - b s - b ë s - a 2 s - a 2 3 3 û T ( s = 2) b é a ù b a 3 1 1 2 ) ) ê1 + s - a ú F ( s + s - b s - a Q ( s s - b ë 3 2 û 3 2 The transfer funct ions can now be ident ified, T ( s = g TF F ( s + g TQ Q ( s ) ) 2) T (...
View Full Document

This note was uploaded on 01/12/2014 for the course CHE 4198 taught by Professor Hjortso,m during the Fall '08 term at LSU.

Ask a homework question - tutors are online